Flexonics for Manufacturing and Robotics Modeling, Design and Analysis Methods - Guo, Jiajie; Lee, Kok-Meng (Research on Intelligent Manufacturing,, 2019)
This book presents the theoretical research and application results of a study on flexible mechatronics (flexonics). Formulating distributed models in both time and spatial domains using a geometric approach, it presents a simple yet practical field-based sensing method for robotics and manufacturing, and illustrates its applications with examples such as exoskeletons, mobile sensor network and intelligent sensing. The book is of interest to researchers, engineers and graduate students in robotics, manufacturing and automation engineering who wish to learn the core principles, theories, technologies, and applications of flexonics. .